Resilience and Emotional Intelligence Related to Workers' Stress Level in the Quarter Life Crisis - Ice Yulia Wardani; Diva Aisyah Oktaviana; Riska Amalya Nasution (Health Science Journal of Indonesia, 2022)
Background: young adults are vulnerable to stress due to difficulty completing their developmental tasks, which would make them be trapped in a quarter-life crisis. Resilience and emotional intelligence are needed to minimize work stress. Objectives: to investigate the relationship between resilience and emotional intelligence with stress levels in workers during the quarter-life crisis. Methods: A quantitative descriptive, correlative, and cross-sectional design was used for the research. Results: 57% of workers had low resilience, 51,9% had good emotional intelligence, and 68,6% experienced moderate stress. The results of the analysis identified a relationship between resilience and emotional intelligence with the stress level of workers during the quarter-life crisis in DKI Jakarta (p=0.001). Conclusions: workers with high resilience and good emotional intelligence experience lower stress than workers with low resilience and low emotional intelligence. This study recommends regular screening of workers’ mental health by health services and also for educational institutes to include material on resilience, emotional intelligence, work stress, and quarter-life crisis. Researchers recommend cooperation between companies and mental health services. Keywords: emotional intelligence, quarter life crisis, resilience, work stress, workers Abstrak Latar Belakang: dewasa muda rentan mengalami stres akibat sulit menyelesaikan tugas perkembangannya, sehingga dapat terjebak pada quarter life crisis. Resiliensi dan kecerdasan emosi dibutuhkan untuk meminimalkan stres kerja. Tujuan penelitian untuk mengetahui hubungan resiliensi dan kecerdasan emosi dengan tingkat stres pekerja pada masa quarter life crisis. Metode: penelitian ini menggunakan desain kuantitatif deskriptif korelatif dan desain cross sectional. Hasil: 57% pekerja memiliki resiliensi rendah, 51,9% pekerja mempunyai kecerdasan emosi baik, dan 68,6% pekerja mengalami stres sedang. Hasil analisis mengidentifikasi adanya hubungan resiliensi dan kecerdasan emosi dengan tingkat stres pekerja pada masa quarter life crisis di DKI Jakarta (p=0,001). Kesimpulan: pekerja dengan tingkat resiliensi tinggi dan kecerdasan emosi baik mengalami stres lebih rendah dibandingkan pekerja dengan resiliensi rendah dan kecerdasan emosi rendah. Penelitian ini merekomendasikan adanya skrining rutin kesehatan jiwa pekerja oleh pelayanan kesehatan serta institut pendidikan untuk memasukkan materi resiliensi, kecerdasan emosi, stres kerja, dan quarter life crisis. Peneliti merekomendasikan adanya kerja sama antara perusahaan dengan layanan kesehatan jiwa. Kata kunci: kecerdasan emosional, pekerja, resiliensi, stres kerja, quarter life crisis